Echocardiographic evaluation of left ventricular function in patients with mitral regurgitation: a meta-analysis - Zhang, Jing; Qiang, Qun (Frontiers in Cardiovascular Medicine, 2025)
PurposeThis study aimed to quantitatively assess left ventricular function in patients with mitral regurgitation (MR) using speckle-tracking echocardiography and further clarify its clinical application.MethodsPubMed, Embase, Web of Science, and Cochrane Library databases were searched from the date of establishment to November 22, 2024. Two investigators independently screened the literature, extracted data, and evaluated the quality of the included studies. Meta-analysis was performed using Stata18.0 software.ResultsFinally, 23 studies were included, all of which scored ≥7 on the Newcastle–Ottawa scale. Meta-analysis results showed that, the left ventricular end-systolic volume index (P < 0.01), left ventricular end-diastolic volume index (P < 0.01), and left ventricular mass index (P < 0.01) of patients with MR were higher than those of healthy individuals. In contrast, the left ventricular ejection fraction (P < 0.01) and global radial strain (GRS) (P < 0.01) of patients with MR was lower than that of healthy individuals; the difference was significant. The E/A of both groups (P = 0.22), global circumferential strain (P = 0.43), global longitudinal strain (P = 0.10), left ventricular relative wall thickness (P = 0.20), and some indexes with significant heterogeneity were analyzed by subgroup according to the degree of MR. The combined results of most subgroup analysis were consistent with the overall results and the heterogeneity was reduced.ConclusionThere is significant difference in the GRS between patients with MR and healthy individuals, which can provide reference for evaluating left ventricular function in patients with MR.